Perlindungan Hukum terhadap Konsumen yang Dirugikan pada Transaksi Elektronik di PT. Orindo Alam Ayu - Ratih Cahya Pramitasari; I Nyoman Putu Budiartha; Ni Made Sukaryati Karma (Warmadewa Press, 2020)
In this Development Era, the rapid development of electronic-based trading. Of course the need for the internet as a medium that connects important online shopping pages. This is what is called E-Commerce, which is a form of electronic-based trading. One company engaged in electronic commerce uses PT. Orindo Alam Ayu. Therefore, the authors are interested in discussing various problems that often occur in this company by pouring in the form of a thesis entitled Legal Protection Against Consumers who are disadvantaged in electronic transactions at PT. Orindo Alam Ayu, with the formulation of the problem 1) How is the legal protection for consumers who are disadvantaged in electronic transactions at PT. Orindo Alam Ayu? 2) How to resolve disputes against consumers who are disadvantaged through electronic transactions at PT. Orindo Alam Ayu? The research method used is empirical research.A loss that is often experienced by consumers who make electronic transactions at PT. Orindo Alam Ayu can do the transfer. Shipping and delivery of goods from PT. Orindo Alam Ayu to the consumer. Consumers take advantage of time, because they have to make complaints to the business, to the channeling of funds, namely banks. Therefore, PT. Orindo Alam Party business assistance here As well as resolving disputes over consumers by fixing money disputes related to each consumer. So the final settlement does not reach the end of the path, licensing can be completed properly.